1946
DOI: 10.1021/ja01205a017
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Capacity and Entropy, Heats of Fusion and Vaporization and the Vapor Pressure of Butene-1. The Zero Point Entropy of the Glass. The Entropy of the Gas from Molecular Data

Abstract: It has been possible to crystallize butene-1 for the first time and thus obtain thermal data on the crystal down to 11.5°K. leading to entropies of crystal, liquid and gas. In addition, it has been possible to cool the glass down to 13°K. and obtain a value for the residual entropy in the glass at the absolute zero.The present paper records the experimental data and conclusions from this work. ExperimentalPurification of Butene-1 Samples.-The sample of butene-1 on which the heat capacities in series I-VIII and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1946
1946
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Z( 1 + KT2/T) exp(-KT2/T) (6) and, finally ASg/ASm = (1 + KT2/Tg) exp(-KY)/(l + KT2/Tm) (60 where Y = TJT" -TJTm.…”
Section: Resultsmentioning
confidence: 99%
“…Z( 1 + KT2/T) exp(-KT2/T) (6) and, finally ASg/ASm = (1 + KT2/Tg) exp(-KY)/(l + KT2/Tm) (60 where Y = TJT" -TJTm.…”
Section: Resultsmentioning
confidence: 99%
“…Systematic deviations are hardly detectable in these cases. All data were used as given by the authors except for the results on 1-butene which are obtained from heat capacity and vapor pressure measurements by Aston et al 92 Here we found that too many assumptions prevent extraction of reliable B-data from these kinds of experiments. The final potential parameters at T ) 0 K and the root-mean-square deviations rms are given in Table 2.…”
Section: U(r T)mentioning
confidence: 99%
“…The value for the entropy of I-butene in the ideal gaseous state at 266.91° K obtained by application of the third law to appropriate calorimetric data is 70.87 ± 0.20 cal/deg mole [18].…”
mentioning
confidence: 92%